2020
DOI: 10.1108/ijppm-12-2019-0593
|View full text |Cite
|
Sign up to set email alerts
|

Developing a framework for evaluating sustainability index for logistics service providers: graph theory matrix approach

Abstract: PurposeThe purpose of this study is to identify sustainability practices and to propose a framework for evaluating the sustainability index of logistics service providers (LSPs).Design/methodology/approachSustainable practices followed by LSPs are identified through literature review and analysis of a case study. Thirteen such sustainable practices are identified. Thereafter, with expert inputs, nine sustainable practices are shortlisted and considered for the evaluation of the sustainability index in the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 86 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…Indeed, the increasing length of global supply chains requires the use of several packaging layers along the supply chain [103]. The investigation presented in [104] proposes a framework for the assessment of the sustainability of logistics service providers. Moreover, due to the diffi-culty of managing supply chains that contain green design, some researchers have analysed the optimisation of green logistics [105], including quantitative methods to evaluate the packaging and logistic design decisions [106].…”
Section: Logistics and Supply Chain Managementmentioning
confidence: 99%
“…Indeed, the increasing length of global supply chains requires the use of several packaging layers along the supply chain [103]. The investigation presented in [104] proposes a framework for the assessment of the sustainability of logistics service providers. Moreover, due to the diffi-culty of managing supply chains that contain green design, some researchers have analysed the optimisation of green logistics [105], including quantitative methods to evaluate the packaging and logistic design decisions [106].…”
Section: Logistics and Supply Chain Managementmentioning
confidence: 99%
“…Graph theory is a graphical representation developed to describe the relationships between proposed factors (Gupta and Singh 2020 ). In this respect, graph theory provides various advantages by analysing system and presenting pair-wise comparisons between factors to investigate relationships of them.…”
Section: Methodsmentioning
confidence: 99%
“…Gupta and Singh (2020a) analyzed performance indicators in the logistics sector of India and observed that the sector needed significant development. It was analyzed for the Asian region that there is link between green logistics performance and environmental and economical degradation (Liu et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%